2019
DOI: 10.1002/jctb.5916
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic electrode improvement strategies in microbial fuel cell systems

Abstract: Microbial fuel cells (MFCs) produce electricity as a result of the microbial metabolism of organic substrates, hence they represent a sustainable approach for energy production and waste treatment. If the technology is to be implemented in industry, low cost and sustainable bioelectrodes must be developed to increase power output, increase waste treatment capacity, and improve service intervals. Although the current application of abiotic electrode catalysts, such as platinum and electrode binders such as Nafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 119 publications
0
15
0
2
Order By: Relevance
“…Cr(VI) reduction could be enhanced by using metal‐reducing bacteria, which shunt electrons from the cathode to the electron acceptor . Inexpensive mode of operation, self‐regeneration of catalysts and sustainable power supply are the advantages of this design over abiotic cathodes . The first attempt to biologically reduce Cr(VI) by means of a biocathode MFC was reported by Tandukar et al .…”
Section: Mfcs With Biocathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr(VI) reduction could be enhanced by using metal‐reducing bacteria, which shunt electrons from the cathode to the electron acceptor . Inexpensive mode of operation, self‐regeneration of catalysts and sustainable power supply are the advantages of this design over abiotic cathodes . The first attempt to biologically reduce Cr(VI) by means of a biocathode MFC was reported by Tandukar et al .…”
Section: Mfcs With Biocathodesmentioning
confidence: 99%
“…49 Inexpensive mode of operation, self-regeneration of catalysts and sustainable power supply are the advantages of this design over abiotic cathodes. 50 The first attempt to biologically reduce Cr(VI) by means of a biocathode MFC was reported by Tandukar et al 12 This study used a conventional H-type MFC with its cathode chamber inoculated with a mixture of denitrifying and anaerobic cultures enriched in the presence of Cr(VI). A Cr(VI) reduction rate of 0.46 mg g −1 volatile suspended solids (VSS) h −1 was achieved and 16S rRNA analysis revealed that the cathode biomass was dominated by putative Cr(VI) reducers Trichococcus pasteurii and Pseudomonas aeruginosa.…”
Section: Mfcs With Biocathodesmentioning
confidence: 99%
“…La producción de electricidad a partir de celdas de combustible microbiana (CCM) consiste en la transformación de energía química en energía eléctrica, debido a la oxidación de los sustratos químicos que contengan microrganismos electrogénicos [1,2]. Una CCM consta de dos electrodos (ánodo y cátodo) y casi siempre una membrana de intercambio protónico (MIP), el proceso de oxidación tiene lugar en el ánodo produciendo electrones los cuales se conducen por un conductor externo hacia el cátodo donde ocurre la reducción, dando así a las reacciones de oxidación/reducción produciendo la corriente eléctrica [3,4] frutas en estado de descomposición [5,6]. Debido a esto los residuos de frutas y aguas residuales se consideran como fuentes de energía en las CCMs en la actualidad [7].…”
Section: Introductionunclassified
“…This ‘In‐focus’ section of the Journal of Chemical Technology and Biotechnology (JCTB) covers a total of six manuscripts (two review papers and four original research articles) in microbial fuel cells reporting recent developments in MFC technology.…”
mentioning
confidence: 99%
“…This improved the bioelectrochemical performance of the MFC. Strategies for improvement of the biocatalytic electrodes are reviewed by Breheny et al . The review covers extensive considerations on bioanode and biocathode and discusses advantages of biocatalysts over abiotic catalysts used in MFC cathodes.…”
mentioning
confidence: 99%